The corporate branding in international operations - Rodrigues, Juliana; Mazzola, Bruno Giovanni; Bassi Sutter, Mariana; Nakazato Miyahira, Ney; Leme Fleury, Maria Tereza (Internext, 2017)
Corporate branding is increasingly gaining relevance in companies’ internationalization; however, few studies directly address the influence and use of corporate branding in processes of internationalization. This study examines these topics and shows the corporate brand as a critical capability in relationships with different stakeholders. A literature review explores corporate branding approaches in international business. In addition, a quantitative exploratory study was conducted using a survey with 297 management-level professionals in Brazil in order to find out if company operation scopes, whether local or multinational, interfere with views on corporate branding. The findings highlight the construction of identity in multinationals as one of the main reasons for adopting corporate brands. However, company operation scopes do not significantly interfere with the hierarchy of reasons perceived as important in the adoption of corporate branding. An emphasis on the concept of corporate branding based on organizational identity was noted among respondents who work at multinationals, showing the relevance of this topic for future research.